A regional algorithm for separating light absorption by chlorophyll-a and coloured detrital matter in the Black Sea, using 480–560 nm bands from ocean colour scanners. Issue 18 (16th September 2016) - Suslin, Vyacheslav; Churilova, Tatyana
ABSTRACT: The aim of this study is to modify the regional algorithm for Moderate Resolution Imaging Spectroradiometer (MODIS) and Medium-spectral Resolution Imaging Spectrometer (MERIS) bands using newly available data of seasonal and spatial variability of light absorption by all optically active components in the Black Sea, and to obtain a merged product based on data retrieved from all the colour scanners that have operated since September 1997. Comparison of chlorophyll- a concentration (chl- a ) simulated by the standard National Aeronautics and Space Administration (NASA) algorithm with in situ chl- a measurements showed that the NASA algorithm provided incorrect chl- a assessment of Black Sea shelf and deep-sea waters during spring‒summer. Originally the standard NASA algorithm could be applied if there was a high correlation between light absorption by phytoplankton ( a ph ) and that by coloured dissolved and suspended organic matter ( a CDM ), which is not the case in the Black Sea. Consequently, development of the correct regional chl- a algorithm requires splitting of light absorption into a ph and a CDM . This issue has been resolved by the proposed regional algorithm developed for the Sea-viewing Wide Field-of-view Sensor (SeaWiFS) using remote-sensing reflectance in three (as minimum) spectral bands from 480 to 560 nm. Operation of the SeaWiFS and MERIS colour scanners ceased in December 2010 and April 2012, respectively, while the MODIS scanner is still working on the Terra and Aqua satellites. In this research, level 2 data (products of standard atmosphere correction at three bands filtered by masks/flags) of SeaWiFS, MODIS (on Terra and Aqua satellites), and MERIS scanners were retrieved for their mission lifetime. The regional algorithm was validated independently for each scanner, based on the adequacy of the algorithm-derived chl- a and a CDM to in situ -measured data for the same day. The results suggest a satisfactory accuracy of the modified regional algorithm.